2020
DOI: 10.1186/s12884-020-03319-7
|View full text |Cite
|
Sign up to set email alerts
|

“I have to provide for another life emotionally, physically and financially”: understanding pregnancy, motherhood and the future aspirations of adolescent mothers in KwaZulu-Natal South, Africa

Abstract: Background Adolescent pregnancy and motherhood has been a controversial and much disputed subject within the field of public health. Early childbearing is not only characterized as a physical body experience but also embodies the experiences and perceptions of the social norms, discourses, conflict and moral judgement. There is an increasing concern that the psychosocial challenges facing adolescent mothers remains in the background since research in this field has mainly focused on the medical… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
84
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(85 citation statements)
references
References 75 publications
1
84
0
Order By: Relevance
“…Unintended pregnancy, a common problem among young people in tertiary institutions, can have a negative impact on their romantic relationships. In a previous study among outof-school adolescent mothers, participants described their relationship with the child's father as complicated [26]. Young women in our study had expectations of support from their partners and unmet expectations resulted in conflict.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…Unintended pregnancy, a common problem among young people in tertiary institutions, can have a negative impact on their romantic relationships. In a previous study among outof-school adolescent mothers, participants described their relationship with the child's father as complicated [26]. Young women in our study had expectations of support from their partners and unmet expectations resulted in conflict.…”
Section: Discussionmentioning
confidence: 72%
“…However, pregnancy came with its own financial demands which sometimes could not be met by the financial resources provided by parents. Similarly, a study among out-of-school adolescent mothers found that they experienced financial difficulties because of reduced financial support from their parents and partners after falling pregnant [26]. Lack of financial resources also affected health seeking behaviour as some participants did not have money for transportation to ANC services.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless our data suggest that this might be an effective approach to maternal suicide prevention in resource constrained environments. Our recommendations for systemic interventions are supported by empirical evidence from LMICs showing the positive impacts on maternal and child health of cash transfers (Bastagli et al, 2019), gender-transformative interventions to promote male engagement in maternal health (Ladur et al, 2021), social support interventions (Bedaso et al, 2021a;Govender et al, 2020;Panday et al, 2009;van den heever et al, 2012) and childcare programmes (Chaturvedi, 2019).…”
Section: Discussionmentioning
confidence: 81%
“…Suicidal thoughts, guilt, loneliness, worry, and stress are among the psychological concerns faced by several adolescent mothers. They also face difficulties returning to school, low socioeconomic level, and social stigmatization [9,56]. Teen moms are more prone to postpartum depression, and infants of teen mothers are more prone to developmental delays and behavioral issues later in life [56].…”
Section: Long-term Consequences Of Adolescent Pregnancymentioning
confidence: 99%